Revitalizing the cultural identity of Bali through spatial planning in Denpasar - I Gusti Putu Anindya Putra (International Journal of Interreligious and Intercultural Studies, 2021)
Bali capital city of Denpasar supposed to reflect a strong Balinese cultural identities, but in reality that cultural identities has declined along of the historical changes and process of development. This study examines the decline of Balinese cultural identities in spatial planning, by focusing it on how to revitalize it and its implications for modern society. Designed has qualitative research, this study collected data through observation, interview, and documentation studies. Data collected analysed by theories geographic and structural functional theories supported by ethnography, semiotics and acculturation theories applied them ecliticly. The results of this study indicate a decline in Balinese cultural identity in spatial planning which has been caused by multicultural community factors, spatial functions that do not exist in the Balinese cultural concept, two forms of traditional village governance and village/kelurahan, as well as changes in the use of the basic dimensions of sikut/gegulak becomes a metric. This study propose strategy of revitalization by reestablishing the values of Balinese cultural identity, cultural literacy, classification and zoning of new functions, synchronizing the authority of traditional villages and villages, and converting basic dimensions into development guidelines. This study offers two findings, that is (1) practical finding relate to the fact that Balinese culture in spatial planning has been applied in the preparation of spatial plans for the city of Denpasar but has not yet been properly implemented; (2) theoretical findings show that Balinese cultural identity in spatial planning is universal, has the ability to absorb elements of external cultures while it is able to maintain its unique cultural identities.